The detection of impending failure in implanted pacemakers. Issue 1 (January 1969) - Davies, J. G.; Siddons, Harold
Abstract : As implantable pacemakers last a variable time, it is desirable to be able to foretell when each individual pacemaker is nearing the end of its life. A test which detects a number of different impending electronic failures including battery depletion is described. The test requires only standard laboratory equipment and has been used for four years as a three-monthly procedure in an out-patient clinic. In 17 of 19 consecutive patients the test has enabled a change of pacemaker to be carried out electively. rather than after an arbitrary period or as an emergency when pacing has failed.